Consumer Protection for Speedboat Service Users at Sri Mersing Beach Tourist Attraction, Serdang Bedagai Regency, Sharia Economic Law Perspective - Dinda Tazkia Aulia; Cahaya Permata (LP2M IAIN Palopo, 2025)
Speedboat services are the main attraction at Sri Mersing Beach, Serdang Bedagai Regency. However, various problems also arise, especially related to the safety of speedboat service users, namely the lack of safety equipment that has the potential to threaten the safety of tourists. This study aims to determine the form of completeness of safety equipment in speedboat services, to determine the regulation of consumer protection for speedboat service users at the Sri Mersing Beach tourist attraction, and to determine these problems from the perspective of Islamic economic law. This type of research is empirical juridical with a living case study approach, statute approach, and conceptual approach. Primary data were obtained through observation and interviews and secondary data were obtained through document studies. Then, the data were processed qualitatively and analyzed using deductive reasoning. The results of the study showed that of the six safety devices that should have been available, only life jackets were available, and even then they were in poor condition. This condition is not in accordance with the mandate of Law Number 8 of 1999 concerning Consumer Protection, Law Number 10 of 2009 concerning Tourism, and Regulation of the Minister of Tourism and Creative Economy Number 4 of 2021. The lack of safety equipment in speedboat services at the Sri Mersing Beach tourist attraction is contrary to the principle of maslahah and the concept of maqashid sharia, especially in the aspect of hifzh al-nafs (protection of life). Therefore, there needs to be regulation, supervision, and education from the government as well as increasing the responsibility of tourism service providers in order to realize tourism that is safe, fair, and in accordance with positive and sharia legal values.